NEURO-LINGUISTIC PROGRAMMING - Mohd Khanapi, Nurul Asyikin; Yahya, Siti Aisyah (Jurnal ’Ulwan, 2023)
Neuro-Linguistic Programming or better known as NLP is a model that is widely used in various fields today. NLP contains ideas and models that claim that it can help individuals to improve themselves and help them achieve their dreams. However, there are those who are not convinced of the validity of NLP due to the lack of evidence to support the narratives and claims presented by NLP practitioners. This study aims to explain the problems found in NLP that cause academics to refuse to use NLP as a method in their field. This study suggests that there is a gap between the claims presented by NLP and the empirical evidence that supports it using past studies as the main source to draw conclusions on the issues presented.